Conservation: naturalisation, - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Conservation: naturalisation, domestication and ecotourismWhen problems arise in forestry, such as disappearing species, or local communities being withheld access to the forest, the usual reaction is to make use of two agroforestry techniques:...